SOME APPLICATIONS OF DNA DATABANKS AS AN INVESTIGATIVE TOOL FOR SOLVING CRIMINAL CASES - Mestres, Francisco; Zivanovic, Goran (NBP. Nauka, bezbednost, policija, 2018)
The introduction of molecular markers, as STR (Short Tandem Repeats) was a fundamental event in Forensic Genetics. It was possible to obtain individual genetic profiles that allowed to properly identifying individuals with small probability of error. Furthermore, police officers soon discovered the investigative value provided by DNA databanks, defined as a collection of individual DNA profiles usually used to investigate crimes and identify suspects. In this article, the authors present the most common use of these police databanks, comment their drawbacks and how to overcome them. The usage and value of police DNA databanks in special criminal situations are also explained: cold cases, familial searches and dragnets. These three particular situations are described and commented in this article. In summary, although several technical, ethical – legal and international aspects have to be improved, police DNA databanks are really powerful investigation tools that allow solving a large number of criminal cases.